Enhancing the Competitive Performance of Catering Enterprises through Knowledge Sharing and Open Innovation - Zhou, Fanze (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study examined the factors influencing knowledge sharing, open innovation, and competitive performance in restaurant firms in Zhanjiang, China. The conceptual framework explored cause-and-effect relationships among Commitment (CO), Shared Language (SL), Shared Vision (SV), Enjoyment in Helping Others (EHO), Knowledge Sharing (KS), Knowledge Hiding (KH), Open Innovation (OI), and Competitive Performance (CP). Research design, data and methodology: A quantitative technique with a sample of 511 practitioners from catering enterprises was employed. Non-probability sampling, comprising judgmental, quota, and convenience methods, was used to select five firms and collect data both online and offline. While effective for targeted data collection, these methods may have limited the generalizability of the findings. Structural equation modeling (SEM) and confirmatory factor analysis (CFA) were used to assess model fit, reliability, and construct validity. Results: The results revealed that CO, SL, and SV significantly enhanced KS, while EHO and KH directly impacted OI. Furthermore, OI positively influenced CP. All seven hypotheses were statistically supported. Conclusions: The findings indicated that fostering organizational commitment, a shared language, and a unified vision promoted effective knowledge sharing, which, along with prosocial behavior and reduced knowledge hiding, drove open innovation. Open innovation, in turn, significantly boosted competitive performance. Managers were encouraged to invest in internal knowledge-sharing mechanisms to strengthen innovation and improve business competitiveness.